Easy Confirmation of Drowning By Detection of Diatoms in Trachea - Shrivastava, Neelam; Satpati, D K; Kumar , Alok (Journal of Indian Academy of Forensic Medicine, 2016)
One of the ways adopted by a person for suicide is drowning. Criminals also hide their crime by throwing person in water after murder. To identify ante mortem drowning or post-mortem drowning, many postmortem findings are considered e.g. hairs and clothing found wet; washer woman‘s appearance in palm and sole; copious leathery froth from mouth and nostrils, etc. But these are not confirmatory and also not present in every case. As, froth also present in poisoning cases and hair and cloth may not be wet if body remains outside water after taking out from alleged place of drowning, therefore to overcome all these fallacies in ante-mortem drowning; presence of diatom in trachea can be considered as a confirmatory test. The conventional Diatom test from bone marrow also has many fallacies and false result. To overcome all these difficulties, the new method is proposed which is easy, less cumbersome, economical and confirmatory test of drowning.
Keywords: Drowning; Tracheal fluid; Diatom; Poisoning